Evaluasi Program Praktek Lapangan Industri Jurusan Teknik Elektro Universitas Negeri Padang - Rezi Ramayanti; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2021)
This study aims to determine the condition of the context, input, process, and product components in the PLI program at the Department of Electrical Engineering, Padang State University. The type of research used in evaluation research with a quantitative approach. This study uses the CIPP context, input, process, and product evaluation model developed by Daniel Stufflebeam with a population of 79 students majoring in electrical engineering who have carried out PLI. The data collection of this research is in the form of a questionnaire. Data analysis techniques used are data verification, data classification, and data processing. The results of this study indicate that the implementation of the PLI program in the Department of Electrical Engineering has been categorized as good, but there are several indicators that must be improved in the future. In the context evaluation, the PLI program objective indicator obtained a respondent's achievement level of 90.54% categorized as very good, the PLI program environmental indicator with a respondent achievement level of 86.75% categorized as good. The input evaluation consists of five indicators, namely supporting facilities with 88% of respondents categorized as good, indicators of sources of funds with 60.8% of respondents being categorized as adequate, program relevance indicators with 85.8% of respondents being categorized as good, indicators of direction, and guidance from majors and industries, the achievement level of respondents was 81.9% categorized as good, and in the Student HR indicator, the achievement level of respondents was 81.4% categorized as good. Process evaluation, indicators of preparation for the implementation of the PLI program with the level of achievement of respondents 84.6% categorized as good, indicators of implementation of the PLI program at the level of achievement of respondents 87.6% categorized as good, indicators of monitoring the implementation of PLI with the level of achievement of respondents 53.5% categorized as not good, and indicators barriers to the implementation of the PLI respondents' achievement level of 83.5% is categorized as good. Product evaluation obtained a respondent's level of achievement of 88.01% which was categorized as good.